Cotton and textiles industries in Tanzania: the failures of liberalisation. (22nd August 2016) - Coulson, Andrew
ABSTRACT: This article uses the story of cotton cultivation in Tanzania to analyse critically the processes of liberalisation and expose the failure of markets to reward quality production. It starts by summarising the technological requirements to grow the crop. It then shows how cotton was central to industrialisation, in Britain and elsewhere. In Tanzania, cotton is grown on small farms and so the article then summarises how small farmers make choices and minimise risks. This creates the context for outline histories, first of cotton growing, and then of textile industries in Tanzania, before turning to the impact of structural adjustment and liberalisation in the late 1980s and 1990s which led to increases in production but losses in quality and price. The article draws conclusions from this about the role of agriculture in processes of economic transformation and the need for institutions which represent the economic interests of small farmers.